Endoscopic versus microscopic discectomy for pathologies of lumbar spine: A nationwide cross-sectional study from a lower-middle-income country - Bhavya Pahwa; Anish Tayal; Dhiman Chowdhury; Giuseppe Emmanuele Umana; Bipin Chaurasia (Journal of Craniovertebral Junction and Spine, 2023)
Objective: We conducted a cross-sectional study to assess the preference of spine surgeons between MD for microdiscectomy and endoscopic discectomy (ED) surgery for the management of lumbar pathologies in a lower-middle-income country (LMIC). Methodology: An online survey assessing the preference of spine surgeons for various lumbar pathologies was developed and disseminated in “Neurosurgery Cocktail” a social media platform. Statistical analyses were performed using SPSS software with a level of significance <0.05. Results: We received responses from 160 spine surgeons having a median experience of 6.75 years (range 0–42 years) after residency. Most of the spine surgeons preferred MD over ED, preference being homogeneous across all lumbar pathologies. In ED, the interlaminar approach was preferred more frequently than the transforaminal approach. The most commonly chosen contraindication for the interlaminar approach and transforaminal approach was ≥ 3 levels lumbar disc herniation (LDH) (n = 117, 73.1%) and calcified LDH (n = 102, 63.8%), respectively. There was no significant association between the type of approach preferred (MD vs. ED; and interlaminar vs. translaminar endoscopic approach) with the type of workplace and the level of experience. Conclusion: Spine surgeons were inclined toward MD over ED, due to various reasons, such as a steep learning curve, lack of training opportunities, and upfront expenses. There is a pressing need for the upliftment of ED in LMICs which requires global action.